Saamskie teatry: między lokalnością a obcością? - Sibińska, Maria (Folia Scandinavica Posnaniensia, 2016)
Institutional theatres in Sapmi have a relatively brief history but they are based upon traditional cultural heritage (the yoik, the art of storytelling, shamanistic seances). At the same time they are open to impulses from other cultures and theatrical traditions (European and non-European) that contribute to the distinct features of Samic theatrical performance when it comes to texts, the aesthetics of performance, and acting traditions. The article outlines the Samic theatre landscape in general and then proceeds to focus on the multicultural aspects of "Ridn'oaivi ja nieguid oaidni", a performance by the Beaivváš Sami Teáhter. The article also calls attention to the problematic nature of the concept "cultural dialogue" in a situation when the borderlines between individual cultures are no longer obvious, and when it is no longer easy to identify the partners in a dialogue unequivocally.